Web designers application sketch book - Kaplan, Dean (Apress, 2011)
Think you have the next great web site idea? The Web Designers Application Sketch Book is an essential tool for any aspiring web designer. This sketch book makes it easy to centralize and organize your ideas, featuring enlarged browser window frame templates to write on. Professionally printed on high-quality paper, it has a total of 150 gridded templates for you to draft ideas and doodle designs while providing ample room to make notes and document the web site name and screen name. This book is an invaluable tool for bringing your next great web site idea to life!